2021
DOI: 10.1038/s41598-021-95006-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of nuclear and mitochondrial DNA from tissue and liquid biopsies of colorectal cancer patients

Abstract: The current standard for molecular profiling of colorectal cancer (CRC) is using resected or biopsied tissue specimens. However, they are limited regarding sampling frequency, representation of tumor heterogeneity, and sampling can expose patients to adverse side effects. The analysis of cell-free DNA (cfDNA) from blood plasma, which is part of a liquid biopsy, is minimally invasive and in principle enables detection of all tumor-specific mutations. Here, we analyzed cfDNA originating from nucleus and mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…Nucleosome occupancy/ ‘footprints’ of cfDNAs may be correlated with the expression of various target genes such as cancer drivers and providing critical information of its tissue of origin [ 205 , 206 ]. More recently, studies have shown a positive correlation between a decrease in nuclear cfDNA levels and a transition to longer fragments, and an improved chemotherapeutic response in patients with CRC [ 207 ]. Conversely, increased and shorter nuclear cfDNA content correlated with tumor recurrence [ 207 ].…”
Section: Emerging Analytes For Liquid Biopsiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleosome occupancy/ ‘footprints’ of cfDNAs may be correlated with the expression of various target genes such as cancer drivers and providing critical information of its tissue of origin [ 205 , 206 ]. More recently, studies have shown a positive correlation between a decrease in nuclear cfDNA levels and a transition to longer fragments, and an improved chemotherapeutic response in patients with CRC [ 207 ]. Conversely, increased and shorter nuclear cfDNA content correlated with tumor recurrence [ 207 ].…”
Section: Emerging Analytes For Liquid Biopsiesmentioning
confidence: 99%
“…More recently, studies have shown a positive correlation between a decrease in nuclear cfDNA levels and a transition to longer fragments, and an improved chemotherapeutic response in patients with CRC [ 207 ]. Conversely, increased and shorter nuclear cfDNA content correlated with tumor recurrence [ 207 ]. cfDNA analysis, thus, offers promising breakthroughs in non-invasive liquid biopsy technologies [ 100 ].…”
Section: Emerging Analytes For Liquid Biopsiesmentioning
confidence: 99%
“…Several features of the mitochondrial genome can be analyzed, such as mtDNA mutations, mtDNA copy number alterations, heteroplasmy, or cf-mtDNA fragment length distribution. Since mtDNA exhibits characteristics distinct from the nuclear genome, including high copy numbers, high mutation frequencies, and heteroplasmy, it may be considered in some novel applications of liquid biopsies [ 98 ]. Recently, some papers have become available on the putative role of cf-mtDNA in CRC screening and follow-up ( Table 4 ).…”
Section: Cell-free Nucleic Acids As Crc Biomarkersmentioning
confidence: 99%
“…Haupts et al reported a higher cf-mtDNA copy number in the plasma of healthy subjects compared to CRC patients [ 98 ]. Copy number of mitochondrially encoded NADH ubiquinone oxidoreductase core subunit 1 ( MT-ND1 ) in blood plasma has been suggested as a marker of early CRC [ 102 ].…”
Section: Cell-free Nucleic Acids As Crc Biomarkersmentioning
confidence: 99%
“…A single normal cell contains only two copies of a nuclear DNA in the nucleus, whereas there are thousands of copies of mitochondrial DNA [ 10 ]. In some types of cancer, such as colorectal and papillary thyroid carcinomas, the proportion of mitochondrial and nuclear DNA circulating in plasma samples is different compared to that of patients without cancer [ 11 , 12 ]. The mitochondrial‐to‐nuclear DNA ratio in the blood of healthy individuals is up to four times higher than in cancer patients [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%